2021
DOI: 10.5194/acp-2021-593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse mixing states of amine-containing single particles in Nanjing, China

Abstract: Abstract. The mixing states of particulate amines with different chemical components are of great significance in studying the formation and evolution processes of amine-containing particles. In this work, the mixing states of single particles containing trimethylamine (TMA) and diethylamine (DEA) are investigated in order to study the formation and aging processes of the single particles using a high-performance single-particle aerosol mass spectrometer located in Nanjing, China, in September 2019. TMA- and D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Chen et al, 2020b). Also, the ion signals with high and low intensity are separated by multichannel acquisition technology and detected simultaneously, which makes the system's dynamic range more than 40 times the traditional data acquisition system and greatly improves the detection of ions with low signals (Shen et al, 2018;Zhong et al, 2021).…”
Section: Sampling Sites and Measurementsmentioning
confidence: 99%
“…Chen et al, 2020b). Also, the ion signals with high and low intensity are separated by multichannel acquisition technology and detected simultaneously, which makes the system's dynamic range more than 40 times the traditional data acquisition system and greatly improves the detection of ions with low signals (Shen et al, 2018;Zhong et al, 2021).…”
Section: Sampling Sites and Measurementsmentioning
confidence: 99%
“…Compared with the traditional SPA-MS, the new HR- Meanwhile, a delayed extraction technology is introduced to improve the mass resolution and increase the hit rate by a factor of 2 ~ 4 for ambient particles (Chen et al, 2020c). Also, the ion signals with high and low intensity are separated by multichannel acquisition technology and detected simultaneously, which makes the system dynamic range more than 40 times of the traditional data acquisition system and improves the detection of ions with low signals greatly (Shen et al, 2018;Zhong et al, 2021).…”
Section: Sampling Sites and Measurementsmentioning
confidence: 99%
“…Generally, the formation of amines in the particle phase, namely aminiums, was related to the gas‐to‐particle partitioning of gaseous amines and acid–base neutralization for their water solubility and alkalinity (Ge et al., 2011b; Qiu & Zhang, 2013; Zhang et al., 2021). The formation of aminiums was favored under high acidity (Ge et al., 2011b), low NH 3 concentration (Chen et al., 2022), high relative humidity (RH; Zhong et al., 2021), and high sulfuric acid concentrations (Zhang et al., 2021). It was also reported that the gas‐to‐particle partitioning of amines can be enhanced through cloud and fog processing (Corral et al., 2022; Rehbein et al., 2011; Youn et al., 2015; Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%